Estimation of demand and supply relationships for beef cattle in Lampung - Atien Priyanti; T.D Soedjana; R Martondang; P Sitepu (Jurnal Ilmu Ternak dan Veteriner, 1998)
An increase in per capita income is followed by an increased demand in number and quality of meat . The purpose of the study was to identify and qualifying factors that influence the demand and supply of beef, and to determine the magnitude of response related to the increase in per capita income. In this study, the time series data from 1970 through 1993 was used and collected from the Directorate General for Livestock Services and Central Bureau of Statistics for the province ofLampung. The parameters observed were production and consumption of beef, retail price, population, per capita income and input price of beef production . A 2SLS method was used to perform the analysis . The results of this study showed that estimated demand and supply relationships using the simultaneous model of2SLS method is appropriate for beef cattle . The results indicated  that retail price of beef is determined simultaneously by demand and supply linkages (P<0.01) . In addition, people in Lampung were responsive enough to anticipate changes on per capita income and lead to the potential for developing Lampung as a strategic beef industry area in Indonesia.   Key words : Supply, demand, beef